(untitled) (Comprehensive Journal of Science, 2025)
This study investigates semantic change in selected Arabic words as used on social media, focusing on Facebook as a model. Adopting a descriptive–analytical approach grounded in semantics and pragmatics, the research examines a small set of high-frequency words that exhibit clear semantic shift, namely: ʾusṭūra (أسطورة), murʿib (مرعب), ḥarīqa (حريقة), jāmid (جامد), and faḫm (فخم). Authentic usage examples were collected from posts and comments on public Facebook pages and accounts during a defined period, then systematically compared with the dictionary meanings of these items as recorded in contemporary Arabic lexicons. The findings show that these words have moved away from their original, predominantly sensory, neutral, or negative fields (myth/falsehood, fear, fire/destruction, rigidity, material luxury) toward new domains characterized by positive evaluative and highly affective meanings. They are now widely used to express praise, admiration, intensity, and high quality, often through metaphorical extension from physical to abstract or symbolic domains. The study also demonstrates the decisive role of the Facebook context—with its rapid interaction, youth-dominated discourse, and preference for exaggeration and informality—in stabilizing these new meanings and making them the salient interpretations for many users. The study concludes by highlighting the need to consider such developments in lexicography and Arabic language teaching, and it recommends further research on semantic change in other digital platforms, semantic fields, and Arabic varieties.